Assessing the Integration of QR codes in Extension Outreach Communication Graphics: A Visual Content Analysis - Kobina D. Fanyinkah; Jefferson D Miller; Casandra Cox; Will Doss (Journal of Applied Communications, 2025)
The purpose of this study was to assess the integration of Quick Response (QR) codes in extension outreach communication graphics with the aim of enhancing extension engagement and information dissemination strategies. A visual content analysis was conducted on QR code-embedded outreach graphics (N = 105) curated from official internet platforms of the [State] co-operative extension service. The graphics were assessed by qualified raters using a codebook based on graphic design principles including color, typography, layout, and visual hierarchy, as well as visual rhetoric attributes. The results revealed strong adherence to fundamental graphic design elements like symmetry (n = 93), balance (n = 92), visual clarity (n = 85) and contrast ( n = 97). However, QR code placement was often supplementary, with only 53% of the sample placing primary emphasis on them. The findings also identified three dominant types of outreach materials—Registration/Survey/Poll (53%), educational/Informational (35%), and Promotional/Event (12%)—and showed 4-H participants as the most frequently targeted audience (n = 70%). While most graphics adhered to professional design standards, only 38% utilized emotional imagery and 56% employed interactive elements indicating potential areas to enhance audience engagement. The study's findings suggest that QR codes should be purposefully placed in extension visual communication designs. To ensure that QR codes are both functional and aesthetically optimized, it is recommended that the extension service engages specific strategies in settings where access to digital content is essential.
Keywords: Extension outreach; QR Codes; Graphics; Visual communication; Graphic design